Savings Accounts and the Life-Cycle Approach to Social Insurance - Peter Birch Sørensen; Martin Ino Hansen; A. Lans Bovenberg (University of Copenhagen, Economic Policy Research Unit (EPRU), 2006)
Using Danish data, we find that about three fourths of the taxes levied to finance public transfers actually finance benefits that do not redistribute between people but redistribute income over the life cycle of individual taxpayers. This provides a rationale for financing part of social insurance via mandatory individual savings accounts. An account system that offers liquidity insurance and a lifetime income guarantee helps to alleviate the dilemma between insurance and incentives. To illustrate this, we analyse a specific proposal for reform of the Danish system of social insurance, involving the use of individual accounts. We estimate how the reform would affect the distribution of lifetime incomes, the public budget, and economic efficiency. Our analysis suggests that, even with conservative assumptions regarding labor supply elasticities, the proposed reform would generate a Pareto improvement and would imply only a minor increase in the inequality of lifetime income distribution.
Keywords: H53; H55; 330; social insurance; individual accounts; lifetime income distribution; Sozialversicherung; Öffentliche Sozialleistungen; Lebenseinkommen; Einkommensverteilung; Dänemark; Verteilungswirkung